The Effect of Niobium Addition on Mechanical Properties and Corrosion Resistance of a Medical Grade SS316L - I Nyoman Jujur; Sri Endah Susilowati; Seto Roseno; Agus Hadi Santosa Wargadipura (Department of Chemical Engineering, Universitas Gadjah Mada, 2021)
To improve mechanical properties, especially elongation, of as-cast medical grade 316L stainless steel, niobium (Nb) was introduced into the alloys, followed by solution heat treatment. Alloying was performed using a 250 kg air induction melting furnace with duplex raw materials and ferronickel. Heat treatment using a solution at 1040 oC, with a holding time of 45 minutes, and water quenching was used. The sample was tested using hardness and ultimate tensile machines. Corrosion tests with simulated body fluids were carried out using media with similar corrosion conditions to human blood. Microstructure observations were performed optically. The results show that the addition of Nb increases the hardness of medical grade 316L stainless steel by 6% compared to the unalloyed steel, both before and after heat treatment. The addition of Nb increases the tensile strength by 8% compared to non-heat treated steel and increases the elongation before and after heat treatment by 8% and 5%, respectively. However, the corrosion rate of the material with Nb is higher than without the addition of Nb. Nb as a carbide former improves the mechanical properties of medical grade 316L stainless steel but adversely affects its corrosion resistance